2022
DOI: 10.1108/rpj-03-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties assessment of a 3D printed composite under torsional and perpendicular stress

Abstract: Purpose This paper aims to evaluate the resin infiltration influence on the mechanical properties of components 3D printed by the material extrusion-based additive manufacturing (AM), also known as fused deposition modeling and commonly uses the acrylonitrile butadiene styrene (ABS) as depositing material. Improvements in their mechanical properties are desirable due failure resulting from the extrusion process. In this way, resin infiltration is considered a candidate solution to enhance 3D printed components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…selection of the material, detail orientation relative to the working platform) on the mechanical properties using incremental technologies. Lovo et al (2022) in their studies assessed the effect of resin infiltration on the mechanical properties produced using additive methods. It was found that the resin infiltration on the ABS material improves the mechanical properties of the manufactured details.…”
Section: Introductionmentioning
confidence: 99%
“…selection of the material, detail orientation relative to the working platform) on the mechanical properties using incremental technologies. Lovo et al (2022) in their studies assessed the effect of resin infiltration on the mechanical properties produced using additive methods. It was found that the resin infiltration on the ABS material improves the mechanical properties of the manufactured details.…”
Section: Introductionmentioning
confidence: 99%